Case report: Successful autologous hematopoietic stem cell transplantation in a patient with GAD antibody-spectrum disorder with rapidly progressive dementia - Disserol, Caio César Diniz; Kowacs, Dora Pedroso; Nabhan, Samir Kanaan; Teive, Hélio Afonso Ghizoni; Kowacs, Pedro André (Frontiers in Neurology, 2023)
The prevalence of neurological syndromes associated with antibodies to glutamic acid decarboxylase is increasing. While cognitive impairment is a common feature of this condition, it seldom emerges as the primary symptom. In this study, we discuss a case of refractory dementia associated with the glutamic acid decarboxylase spectrum disorder. Interestingly, this case showed a favorable outcome following autologous hematopoietic stem cell transplantation. We also provide an in-depth review of the current literature on the use of this therapeutic approach for the treatment of this disease.